Current medical diagnosis & treatment 2011 - McPhee, Stephen J.; Papadakis, Maxine A. (New York : McGraw-Hill Medical, 2011)
Comprehensive in its coverage of inpatient and outpatient care, and uniquely accessible in reinforcing only those diagnostic and treatment tools pertinent to practice, this book is the ultimate clinical companion.
Chapter 1. Disease prevention & health promotion -- Chapter 2. Common symptoms -- Chapter 3. Preoperative evaluation & perioperative management -- Chapter 4. Geriatric disorders -- Chapter 5. Palliative care & pain management -- Chapter 6. Dermatologic disorders -- Chapter 7. Disorders of the eyes & lids -- Chapter 8. Ear, nose, & throat disorders -- Chapter 9. Pulmonary disorders -- Chapter 10. Heart disease -- Chapter 11. Systemic hypertension -- Chapter 12. Blood vessel & lymphatic disorders -- Chapter 13. Blood disorders -- Chapter 14. Disorders of hemostasis, thrombosis, & antithrombotic therapy -- Chapter 15. Gastrointestinal disorders -- Chapter 16. Liver, biliary tract & pancreas disorders -- Chapter 17. Breast disorders -- Chapter 18. Gynecologic disorders -- Chapter 19. Obstetrics & obstetric disorders -- Chapter 20. Musculoskeletal & immunologic disorders -- Chapter 21. Electrolyte & acid-base disorders -- Chapter 22. Kidney disease -- Chapter 23. Urologic disorders -- Chapter 24. Nervous system disorders -- Chapter 25. Psychiatric disorders -- Chapter 26. Endocrine disorders -- Chapter 27. Diabetes mellitus & hypoglycemia -- Chapter 28. Lipid disorders -- Chapter 29. Nutritional disorders -- Chapter 30. Common problems in infectious diseases & antimicrobial therapy -- Chapter 31. HIV infection and AIDS -- Chapter 32. Viral & rickettsial infections -- Chapter 33. Bacterial & chlamydial infections -- Chapter 34. Spirochetal infections -- Chapter 35. Protozoal & helminthic infections -- Chapter 36. Mycotic infections -- Chapter 37. Disorders related to environmental factors -- Chapter 38. Poisoning -- Chapter 39. Cancer -- Chapter 40. Clinical genetic disorders -- Chapter 41. Complementary & alternative medicine -- Appendix: Therapeutic drug monitoring & laboratory reference intervals.
Includes bibliographical references and index.
Keywords: Diagnosis; Medicine; Therapeutics